Improving WRF‐Hydro runoff simulations of heavy floods through the sea surface temperature fields with higher spatio‐temporal resolution. Issue 9 (9th September 2021) - Kilicarslan, Berina Mina; Yucel, Ismail; Pilatin, Heves; Duzenli, Eren; Yilmaz, Mustafa Tugrul
Abstract: This study investigates the impact of the spatio‐temporal accuracy of four different sea surface temperature (SST) datasets on the accuracy of the Weather Research and Forecasting (WRF)‐Hydro system to simulate hydrological response during two catastrophic flood events over the Eastern Black Sea (EBS) and the Mediterranean (MED) regions of Turkey. Three time‐variant and high spatial resolution external SST products (GHRSST, Medspiration and NCEP‐SST) and one coarse‐resolution and time‐invariant SST product (ERA5‐ and GFS‐SST for EBS and MED regions, respectively) already embedded in the initial and the boundary conditions datasets of WRF model are used in deriving near‐surface atmospheric variables through WRF. After the proper event‐based calibration is performed to the WRF‐Hydro system using hourly and daily streamflow data in both regions, uncoupled model simulations for independent SST events are conducted to assess the impact of SST‐triggered precipitation on simulated extreme runoff. Some localized and temporal differences in the occurrence of the flood events with respect to observations depending on the SST representation are noticeable. SST products represented with higher cross‐correlations (GHRSST and Medspiration) revealed significant improvement in flood hydrographs for both regions. The GHRSST dataset shows a substantial improvement in NSE ( 70%), RMSE reduction up to 20%, and an increase in correlation from 0.3 to 0.8 with respect to the invariable SST (ERA5) in simulated runoffs over the EBS region. The use of both GHRSST and Medspiration SST data characterized with high spatio‐temporal correlation resulted in runoff simulations exactly matching the observed runoff peak of 300 m 3 /s by reducing the overestimation seen in invariable SST (GFS) in the MED region. Improved precipitation simulation skills of the WRF model with the detailed SST representation show that the hydrographs of GHRSST and Medspiration simulations show better performance compared to the simulated hydrographs by observed precipitation. Abstract : Impact of the spatio‐temporal accuracy of four different SST datasets (GHRSST, Medspiration, NCEP‐SST and ERA5‐ and GFS‐SST for Eastern Black Sea (EBS) and Mediterranean (MED) regions, respectively) on the hydrological response predicted by WRF‐Hydro modelling system is assessed for catastrophic flood events occurred in EBS and MED regions of Turkey. Results show that especially Medspiration and GHRSST characterized with high spatio temporal correlation shows the best statistical improvement in the model runoff predictions compare to the other SST datasets.